The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000006988
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of peripheral artery disease with Sildenafil and Bosentan combined therapy in a patient with limited cutaneous systemic sclerosis

Abstract: Rationale:Sildenafil, a phosphodiesterase-5-inhibitor and Bosentan, an endothelin-1-receptor antagonist combined therapy could have beneficial effect in systemic sclerosis (SSc) patients with peripheral artery disease.Patient concerns:We report a case of a 48-year-old Black woman, who developed severe left limb claudication and walking limitation following a left femoropopliteal bypass occlusion in 2014. She was a heavy smoker and had a history of right middle cerebral artery ischemic stroke and bilateral Rayn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[8] Other case reports have shown improvements in PAD-related diseases by the use of SC. [10,11] No side effects related to the continued use of SC was reported, and safety issues restrained to care related to the known side effects of SC (patients using nitrites or with electrocardiographic abnormalities suspected of ischemic cardiovascular alterations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Other case reports have shown improvements in PAD-related diseases by the use of SC. [10,11] No side effects related to the continued use of SC was reported, and safety issues restrained to care related to the known side effects of SC (patients using nitrites or with electrocardiographic abnormalities suspected of ischemic cardiovascular alterations).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SC has been shown to improve glucose metabolism in diabetic patients [7,8]. Daily usage of SC for three months was shown to enhance the insulin sensitivity and to improve the markers of endothelial function [9][10][11]. A mechanism has been proposed correlating improvement in the microcirculation with nitric oxide synthase (type III) activation, which becomes calcium independent upon phosphorylation by cyclic nucleotidedependent protein kinases [12].…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 17 For severe refractory ischaemia as in this case, Sildenafil, a phosphodiesterase 5 inhibitor, is normally added. 18 Its effect is also to improve perfusion leading to complete resolution of DUs and lower the risk of new ulcer formation. 19 , 20 Combination therapy of Bosentan and Sildenafil was not possible for her on account of persistently low blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the current literature found only four papers in which combination therapy has been used in RP and DU associated with SSc including three case reports 911 and a single retrospective monocentric study, which reported the effect of bosentan and sildenafil on NVC and clinical improvement. 12 Table 1 summarizes these papers and the respective treatment regimens used in each case.…”
Section: Discussionmentioning
confidence: 99%
“…After the addition of bosentan, walking distance improved considerably and limb claudication symptoms were greatly improved. 11…”
Section: Discussionmentioning
confidence: 99%